Synthesis of Some New Pyrazoline Compounds Derived from α-β Unsaturated Compounds and Study their biological and Biochemical Effect - Wissam M. R. Al-Joboury (Journal of Global Pharma Technology, 2020)
In this work Compounds Chalcones (w1-8) have been prepared from the reaction of acetophenone derivatives with appropriable aromatic aldehyde in presence of Noah (10%). The reaction of thiosemicarbazide with chalcones (w1-8) yielded compounds (W9-16) 5- (Aryl) -3- (4-sub. Phenyl) 4-5-dihro -1H-Pyrazole -1- Carbathiamide). All the new compounds have been characterized by using spectral (IR, H1-NMR, TLC) data. And physical methods. The antibacterial activity have been tested in vitro by the disk diffusion assay method against two kinds of bacteria gram positive and gram negative .The minimum inhibitory concentration [MIC] have been determined with the reference of standard drugs the results showed that the pyrazoline derivatives are better than growth of both types of bacteria (gram- positive and germ–negative compared to drug .The effect of hydrogen peroxide (0.1%) H2O2 drinking water through the mouth for about (15) days on white male rats shows significant increase (P˂0.01) at the level glucose and cholesterol and Triglyceride in the serum comparison with the control group, where as it shows a significant decrease(P˂0.01) in the level of ,glutathione, glutathione Peroxidase (GSH-Px), Superoxide dismutase (SOD), in serum. Whereas the prepared (W11) compound was injected, results show after (5) days of treatment that the organic compound of (7.14) mg/kg of body weight through the mouth for white male rats exposed to oxidation, with an associated significant decrease (P